De frente para a tela: as implicações do uso das plataformas digitais no contexto da pandemia da COVID-19 nas percepções dos professores da educação básica de Mato Grosso do Sul - Theodoro, Yasmine Braga (Universidade Federal de São Carlos, 2025)
The adoption of Emergency Remote Teaching (ERT) during the SARS-CoV-2 (Covid-19) pandemic forced educational systems to adapt their practices to ensure the continuity of activities remotely. In the state of Mato Grosso do Sul (MS), this adaptation involved a reorganization of teaching work in schools, with increased use of digital platforms and the adoption of technological services for education. This research seeks to understand the introduction and expansion of digital platforms in the State Education Network (REE) during the aforementioned health crisis and investigate the perceptions of teachers and administrators regarding this phenomenon, focusing on the intensification and precariousness of teaching work. The hypothesis was that the combination of the pandemic and increased use of digital platforms exacerbated teachers' precarious working conditions. Therefore, the aim was to understand the new forms of teaching work management through Complementary Pedagogical Activities (CPAs), associated with the use of Information and Communication Digital Technologies (ICDTs), and the phenomenon of platformization. Additionally, it sought to investigate Google's role in Basic Education and compare teachers' and administrators' perceptions of the use of its platforms during ERT, identifying whether changes in work organization persisted upon returning to face-to-face teaching. To achieve this, the research used a mixed methodology, combining the application of questionnaires with REE/MS teachers to obtain quantitative data on the use of digital platforms, with semi-structured interviews that further explored their perceptions on the subject. The results indicated that, although digital platforms were necessary tools for the continuity of teaching during the pandemic period, they also imposed an increased workload on teachers in Mato Grosso do Sul and accentuated inequalities in access to technologies, contributing to the precarization of teaching work during ERT.

La adopción del Enseñanza Remota de Emergencia (ERE) durante la pandemia de SARS-CoV-2 (Covid-19) obligó a los sistemas educativos a adaptar sus prácticas para garantizar la continuidad de las actividades de manera remota. En el estado de Mato Grosso do Sul (MS), esta adaptación implicó una reorganización del trabajo docente en las escuelas, con un aumento en el uso de plataformas digitales y la adopción de servicios tecnológicos para la educación. Esta investigación busca comprender la introducción y expansión de las plataformas digitales en la Red Estatal de Educación (REE) durante la mencionada crisis sanitaria e investigar las percepciones de profesores y gestores sobre este fenómeno, centrándose en la intensificación y precarización del trabajo docente. La hipótesis fue que la combinación de la pandemia y el aumento del uso de plataformas digitales exacerbó las precarias condiciones laborales de los profesores. Por lo tanto, el objetivo fue comprender las nuevas formas de gestión del trabajo docente a través de las Actividades Pedagógicas Complementarias (APCs), asociadas al uso de Tecnologías Digitales de la Información y la Comunicación (TDICs), y el fenómeno de la plataformaización. Además, se buscó investigar el papel de Google en la Educación Básica y comparar las percepciones de los docentes y gestores sobre el uso de sus plataformas durante el ERE, identificando si los cambios en la organización del trabajo perduraron al retornar a la enseñanza presencial. Para ello, la investigación utilizó una metodología mixta, combinando la aplicación de cuestionarios a los profesores de la REE/MS para obtener datos cuantitativos sobre el uso de plataformas digitales, con entrevistas semiestructuradas que profundizaron en sus percepciones sobre el tema en cuestión. Los resultados indicaron que, aunque las plataformas digitales fueron herramientas necesarias para la continuidad de la enseñanza durante el período pandémico, también impusieron una carga de trabajo adicional a los profesores en Mato Grosso do Sul y acentuaron las desigualdades en el acceso a las tecnologías, contribuyendo a la precarización del trabajo docente durante el ERE.
Facing the screen: implications of digital platform use during the COVID-19 pandemic for basic education teachers in Mato Grosso do Sul
De frente a la pantalla: las implicaciones del uso de plataformas digitales en el contexto de la pandemia de COVID-19 según las percepciones de los docentes de educación básica de Mato Grosso do Sul
Keywords: Ensino remoto emergencial; Plataformas digitais; Trabalho docente; Precarização do trabalho; Tecnologias digitais de informação e comunicação; Educação pública; Emergency remote teaching; Digital platforms; Teaching work; Precarization of work; Information and communication technologies; Public education; Enseñanza remota de emergencia; Plataformas digitales; Trabajo docente; Precarización del trabajo; Tecnologías digitales de la información y la comunicación; Educación pública; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS